Barômetro de gestão de processos: um modelo de benchmarking para instituições de ensino superior - Mendonça, Matheus de Melo (Universidade Federal Rural do Semi-Árido, 2021)
The Federal Higher Education Institutions (FHEIs), as well as other organizations, work with scarce resources, requiring an efficient management of them. From this perspective, Bussines Process Management (BPM) can contribute to a better performance of this type of organization, so that it provides a service that meets the citizen's expectations. However, despite the existence of studies involving BPM and Higher Education Institutions (HEIs), the context of these researches is local, and no researches that evaluate the level of maturity of these institutions in terms of process management in a national perspective have been identified. Thus, there is a need for a reference model through which the HEIs can be regularly evaluated regarding their level of maturity in process management, identifying the reference institutions in this management model. With this in mind, this research proposes a participative multi-criteria benchmarking model to classify Higher Education Institutions as to their level of maturity in process management. The research method was divided into three stages: (i) construction of the evaluation model, (ii) data collection, and (iii) classification of the FHEIs as to the level of maturity in process management. In the first stage, the criteria for evaluating the level of maturity in process management in a HEI were established by means of the Delphi technique with the participation of experts and, by means of a consensus meeting for preference elicitation, the relative importance of each criterion represented by weights. In the second stage, the performance of the FHEIs was collected by means of a selfassessment questionnaire established based on the criteria defined in the previous stage. The data were collected from 31 Brazilian FHEIs from the five regions of the country. In the third step, the FHEIs were classified as to their maturity level in process management using the PROMSORT multicriteria decision support method. Sensitivity analysis was performed by simulating scenarios established from the variation of criteria weights and points of view adopted for the classification. The results showed that regardless of the adoption of an optimistic or pessimistic perspective, the majority of the FHEIs (51.6% in the optimistic perspective and 54.8% in the pessimistic one) were classified as regular. Furthermore, approximately 80% of the participating FHEIs maintained their classifications, and among the six alternatives that presented classication variations, only three presented significant variability caused by sensitivity to the adopted classification point of view. Thus, the stability of the results obtained by means of the developed model is verified. The analyses indicate that Brazilian FHEIs commonly have BPM initiatives, but, in many cases, they still lack the necessary practices to reach a significant maturity at a national level. Finally, the viability of using this model as a subsidy for the development of a benchmarking web platform capable of creating a virtual environment conducive to the search for best practices in process management in HEIs is perceived
Keywords: Benchmarking; Gestão de processos de negócio (BPM); Instituições de ensino superior (IES); PROMSORT; Business Process Management (BPM)).; Higher Education Institutions (HEI’s); ENGENHARIAS::ENGENHARIA DE PRODUCAO